Epigenetic mechanisms in epilepsy - Kobow, Katja; Blümcke, Ingmar (Progress in Brain Research, 2014)
In humans, genomic DNA is organized in 23 chromosome pairs coding for roughly 25,000 genes. Not all of them are active at all times. During development, a broad range of different cell types needs to be generated in a highly ordered and reproducible manner, requiring selective gene expression programs. Epigenetics can be regarded as the information management system that is able to index or bookmark distinct regions in our genome to regulate the readout of DNA. It further comprises the molecular memory of any given cell, allowing it to store information of previously experienced external (e.g., environmental) or internal (e.g., developmental) stimuli, to learn from this experience and to respond. The underlying epigenetic mechanisms can be synergistic, antagonistic, or mutually exclusive and their large variety combined with the variability and interdependence is thought to provide the molecular basis for any phenotypic variation in physiological and pathological conditions. Thus, widespread reconfiguration of the epigenome is not only a key feature of neurodevelopment, brain maturation, and adult brain function but also disease.
EVALuna2:7267